Cijene prometnih usluga u funkciji integracijskih procesa u Evropi - Bogović, Blaž; Perak, Mato; Radačić, Željko (Promet - Traffic&Transportation, 2012)
Owing to some specific aspects of the transport service market there has always been present a minor or major impact of the state upon the fixing of transport service costs or the policy of investments into the traffic infrastructure. Currently we have the processes of deregulation going on, on one hand, and strengthening of the market functions on the other. In such circumstances one should expect in the future that the fixing of transport service rates is more and more affected by the economic factor which means that as with the costs/prices of goods and services in other industries the fares/transport service charges will be subject to a permanent impact of numerous market factors acting within the scope of the national market yet more and more with respective reflections of all regional and global economic trends.